A Bidirectional Semi-Passive DS-CDMA-RFID Transponder for the UHF Band - Löffler, Andreas; et al. (ICWMC 2011, The Seventh International Conference on Wireless and Mobile Communications, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.komele.abidir

A Microcontroller-based HF-RFID Reader Implementation for the SD-Slot - Löffler, Andreas; et al. (DigitalWorld 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.komele.amicro

A Multi-Purpose RFID Reader Supporting Indoor Navigation Systems - Löffler, Andreas; Gerhäuser, Heinz; Kuznetsova, Dina; Wissendheit, Uwe (2010 IEEE International Conference on RFID-Technology and Applications (RFID-TA), 2010)
In this paper we introduce an UHF-RFID reader system built to serve as a multi-purpose reader for UHF-RFID applications. The structure of the reader itself is highly flexible to be able to include several standards. The intended use of the reader, however, consists in the support of navigation systems for the indoor environment. Assuming that arbitrarily distributed RFID tags, containing their exact positions given in latitude, longitude and elevation, are read out by the reader, the system is able to achieve the tags positions. In that case, the reader is able to evaluate and forward the readout positions in order to notify a superior navigation system of the estimated position, obtained from the RFID tags. This will lead to a more robust navigation system being able to navigate even in a high-grade multipath environment. Anyway, this paper concentrates more on technical terms concerning the reader system, including signal and spectrum analysis. © 2010 IEE
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.amulti

Analysis of the applicability of RFID & wireless sensors to manufacturing and distribution lines trough a testing multi-platform - Löffler, Andreas; Wissendheit, Uwe; et al. (2010 IEEE International Conference on Industrial Technology (ICIT), 2010)
The increasing number of product references involved in production and distribution lines, implies an added complexity for the management and control systems of companies. Moreover, customers are increasingly in favour of the use of new technology when placing their orders, such as on-line booking and purchasing, and their requirements are increasingly greater. Customers, as well as companies, are demanding updated information on the condition and location of their ordered products during fabrication and transportation phases. This paper proposes an analysis of the applicability of accessing information in real-time related to a product's condition along the manufacturing and supply chain, by means of the integration of RFID systems with sensors and wireless networks. To achieve this purpose a multi-service controller board has been designed into which specific operation modules are plugged. The modules are active or passive RFID readers, modules with sensors or actuators, or modules for data storage. Furthermore, some other communication modules have also been developed offering WLAN, ZigBee or GPRS networks. Using these solutions, companies will have a more reliable and faster access to information in different areas of manufacturing and logistics. Their ease of implantation and reliability makes the use of the systems analysed here, an ideal solution for companies who wish to monitor over their manufacturing and distribution lines more easily. In addition, when all this technology works together, new functions and applications appear with interesting results for the different case studies. ©2010 IEE
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.analys

A Novel Approach for UHF-RFID-Based Positioning Through Spread-Spectrum Techniques - Löffler, Andreas; Gerhäuser, Heinz (RFID SysTech 2010, 6th European Workshop on Smart objects: Systems, Technologies and Applications, 2010)
UnivIS-Import:2015-07-08:Pub.2010.tech.IE.komele.anovel

An RFID Reader Network Based on SOAP - Popp, Christian; Wissendheit, Uwe; Löffler, Andreas (RFID SysTech 2010, 6th European Workshop on Smart objects: Systems, Technologies and Applications, 2010)
UnivIS-Import:2015-07-08:Pub.2010.tech.IE.komele.anrfid

An UHF RFID Reader for Cell Phones - Löffler, Andreas; et al. (2010 International Conference on Wireless Information Technology and Systems, 2010)
This paper presents a mobile, cell phone-based UHF RFID reader. The UHF reader is based on a single chip solution with few external components, currently working as USB client at the cell phone's USB host connection. Therefore, our work describes a fully functional UHF RFID reader connected to the cell phone, providing power and communication capabilities. © 2010 IEE
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.anuhfr

Applikationsunterstuetzung durch LabVIEW im RFID-Bereich - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe (Virtuelle Instrumente in der Praxis, 2008)
UnivIS-Import:2015-04-20:Pub.2008.tech.IE.komele.applik_4

A SOAP capable HF-RFID-Reader - Löffler, Andreas; Gerhäuser, Heinz; Hoffmann, Martin; et al. (RFID SysTech 2008, 4th European Workshop on RFID Systems and Technologies, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.komele.asoapc_4

Ausgewählte Projekte: Radio Frequency IDentification - Löffler, Andreas; et al. (Lehre und Forschung am Lehrstuhl für Informationstechnik, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.komele.ausgew_9

CDMA-Based UHF-RFID System with Semi-Passive UHF Transponders - Löffler, Andreas; Schuh, Fabian; Altmann, Ingo (2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.komele.cdmaba

Dispersion Effects at High Bandwidth Localization for UHF RFID Tags - Löffler, Andreas (Smart SysTech 2012 European Conference on Smart Objects, Systems and Technologies, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.disper

Eine RFID-basierte Roboternavigationslösung - Löffler, Andreas; Lurz, Fabian (Virtuelle Instrumente in der Praxis: Begleitband zum Kongress VIP 2010, 2010)
UnivIS-Import:2015-04-20:Pub.2010.tech.IE.komele.einerf

Ein flexibles Multi-RFID-Reader-System unter Verwendung der SOAP-Schnittstelle - Löffler, Andreas; et al. (Virtuelle Instrumente in der Praxis, Begleitband zum Kongress VIP 2009, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.komele.einfle_1

Extended Localizing with NFC-capable cell phones - Löffler, Andreas (Program of 4th Annual IEEE International Conference on RFID, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.extend

GIDS - A system for combining RFID-based site information and web-based data for virtually displaying the location on handheld devices - Löffler, Andreas; Gerhäuser, Heinz; Kuznetsova, Dina; Wissendheit, Uwe (2008 IEEE International Conference on RFID, 2008)
This paper describes an application that uses RFID information to display location-based coordinates on a map. An RFID transponder containing the coordinates of the transponder's position as well as optional information, e.g. about the location, building, neighborhood, is read out by a specially developed RFID reader. The reader processes the information and forwards it to a handheld device, which is wireless connected to a database/intranet or the Internet. In a first step this handheld device is a Tablet PC running a software application, which processes the data received from the transponder and maps the transponder's position on a graphical output. The graphical output is based on the Google Maps environment and implemented in a web browser plugin. For this purpose, the software application uses specific scripts (implemented in JavaScript), which generate standard and custom maps based on the Google Maps API. In a second step, the application has been ported to a mobile platform, consisting of a mobile phone, with a NFC capable RFID reader. © 2008 IEE
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.komele.gidsas

Improving the Combination of RFID with Other Technologies by Means of a Multi-service Device - García-Escribano, Javier; García, Andrés; Löffler, Andreas; Pastor, Jose; et al. (RFID SysTech 2010, 6th European Workshop on Smart objects: Systems, Technologies and Applications, 2010)
Complexity in management and control systems of companies is growing everyday. The increasing number of product references involved in production and distribution lines, together with the demand of customers and companies for having updated information of their ordered products are contributing enormously. Moreover, customers are increasingly in favour of the use of new technology when placing their orders, such as on-line booking and purchasing, and their requirements are increasingly greater. These requirements of flexibility and access to information have often been achieved by means of the combination of RFID systems, networks of sensors, etc. However, for companies, it is not always easy to find the best combination of technology. This paper proposes the integration of RFID systems with sensors and wireless networks using one single multi-service controller board. With this device, an analysis of the application of accessing information in real-time, related to a productÂ¿s condition along the manufacturing and supply chain, has been made possible. To achieve this purpose, several specific operation modules connect with the main board. The modules are active or passive RFID readers, modules with sensors or actuators, or modules for data storage. Furthermore, some other communication modules have been connected to form WLAN, ZigBee or GPRS networks. The use of this device provides a flexible and adaptable solution for companies which look for the best technology to use. Using it, companies have a more reliable and faster access to information in many manufacturing and logistics scenarios. The advantages are clear when all this technology works together: new functions and applications appear with interesting results for different case studies.
UnivIS-Import:2015-07-08:Pub.2010.tech.IE.komele.improv
Keywords: Antennas; Ground penetrating radar; Humidity measurement; Routing; Wireless LAN; Wireless sensor networks; Zigbee

Indoor Positioning System with Android Smartphone Using UHF-RFID Technology - Löffler, Andreas; et al. (X International Scientific Conference on Physics and Radioelectronics in Medicine and Ecology (PREME 2012), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.komele.indoor

Inductively-Charged and Temporarily Self-Sufficient Operating Sensor Using Standard RFID-HF Technology - Löffler, Andreas; Gerhäuser, Heinz; Kuznetsova, Dina; Wissendheit, Uwe (RFID SysTech 2009, 5th European Workshop on RFID Systems and Technologies, 2009)
UnivIS-Import:2015-07-08:Pub.2009.tech.IE.komele.induct

Integration of RFID-Technologies into the Hospital Information System - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe (Zukunftstechnologien in der Nachrichtenübertragung, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.komele.integr

LabVIEW als zentrales Element zur Vernetzung, Visualisierung und Messautomatisierung - Löffler, Andreas; et al. (Virtuelle Instrumente in der Praxis, Begleitband zum Kongress VIP 2007, 2007)
UnivIS-Import:2015-04-20:Pub.2007.tech.IE.komele.labvie_1

LabVIEW als zentrales Element zur Vernetzung, Visualisierung und Messautomatisierung - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe (2007)
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.komele.labvie

LabVIEW basiertes Messsystem zur Abstandsbestimmung zwischen einem RFID Transponder und einem Lesegerät - Löffler, Andreas; et al. (Virtuelle Instrumente in der Praxis, Begleitband zum Kongress VIP 2009, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.komele.labvie_1

Localizing passive UHF RFID tags with wideband signals - Löffler, Andreas (Microwaves, Communications, Antennas and Electronics Systems (COMCAS), 2011 IEEE International Conference on, 2011)
Applications using localization of passive UHF RFID tags include, among others, indoor and assistant navigation (e.g., together with GPS), logistics, etc. This work shows a method to determine the distance between a tag and a reader by using passive UHF RFID tags and low power wideband signals. The passive UHF RFID tag is emulated through an antenna with varying load impedances. The work shown in this paper presents some first experimental results of such a ranging system. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.komele.locali

Localizing with Passive UHF RFID Tags Using Wideband Signals - Löffler, Andreas; Gerhäuser, Heinz (Radio Frequency Identification from System to Applications, 2013)
UnivIS-Import:2015-04-20:Pub.2013.tech.IE.komele.locali

Lokalisierung mittels RFID im UHF-Bereich mit passiven RFID-Tags - Löffler, Andreas (Lehre und Forschung am Lehrstuhl für Informationstechnik, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.komele.lokali

Messgärete vernetzen und visualisieren sowie Messaufgaben automatisieren - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe (2008)
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.komele.messgr

Radio Frequency IDentification (RFID) - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe (Lehre und Forschung am Lehrstuhl für Informationstechnik, 2009)
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.komele.radiof

Realization of a CDMA-based RFID System Using a Semi-Active UHF Transponder - Löffler, Andreas; et al. (2010 Sixth International Conference on Wireless and Mobile Communications, 2010)
RFID systems may increase the efficiency of logistic systems, e.g., inventory of stocks. Unfortunately, present existing systems come fast to their limits if a great amount of RFID transponder must be inventoried in very short time, as the channel access method of current RFID systems is Time Division Multiple Access. To shorten the inventory process, this work shows a first realization of an RFID-based semi-active UHF transponder using a Code Division Multiple Access method. The work concentrates on the uplink channel (tag to reader) that covers the transponder's backscattered signals. This channel access method enables simultaneous transfer of data, meaning that all transponder in the field may respond at the same time within the same frequency band. The data transfer realized for the uplink channel, uses a certain set of orthogonal spreading sequences (modified Gold codes) being different for every transponder. The RFID reader used in this work despreads the backscattered signals and decodes the data of the different transponder. Briefly, this work shows, in principle, the opportunity for a simultaneous data transfer on the uplink channel in RFID systems, which in turn may shorten very much the time for a complete inventory round. © 2010 IEE
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.realiz
Keywords: rfid; cdma; uplink; uhf; transponder

RFID in medical applications - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe; et al. (Proceedings 8th International Conference on Physics and Radio-electronics in Medicine and Ecology (PHREME 2008), 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.komele.rfidin

Simple Navigation with RFID-enabled cell phones - Löffler, Andreas; et al. (2010 International Conference on Indoor Positioning and Indoor Navigation (IPIN), 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.simple

Stochastic and Deterministic Broadband UHF RFID Channel Models for Indoor Localization - Löffler, Andreas; Gerhäuser, Heinz (ITG-Fachbericht 243, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.stocha

UHF-RFID-Based Localization Using Spread-Spectrum Signals - Löffler, Andreas (GlobeNet 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.komele.uhfrfi
Keywords: Radiofrequency identification; Spread spectrum; Wideband; Communication channels

Using CDMA as Anti-Collision Method for RFID - Research & Applications - Löffler, Andreas (Current Trends and Challenges in RFID, 2011)
UnivIS-Import:2015-04-20:Pub.2011.tech.IE.komele.usingc

Using RFID-capable cell phones for creating an extended navigation assistance - Löffler, Andreas; Kuznetsova, Dina; Wissendheit, Uwe (Microware and Optoelectronics Conference (IMOC),2009 SBMO/ IEEE MTT-S International, 2009)
This paper offers an RFID-based indoor navigation application which utilizes cell phones with an RFID extension and distributed RFID tags fixed to interior equipment. This combination creates a special navigation environment which helps pedestrians to orient oneself in new respectively unknown environments. Therefore, each RFID tag contains information about the current position, location or an unknown environment. Thus, the current position can be determined, which is the basic for navigation. A further advantage of this application is the availability of additional graphical data stored on the RFID tags. This additional graphical data contains global information about the indoor environment and also local graphical information about the near environment of the RFID tag. This yields to an RFID-based navigation system, that not only shows the current position but also the near environment surrounding that specific location. Therefore, this systems grants navigation assistance by leading the user step-by-step or rather tag-by-tag to the final destination. ©2009IEEE.
UnivIS-Import:2015-04-20:Pub.2009.tech.IE.komele.usingr_7